Analisis Prinsip Kerja Sama Antartokoh dalam Dialog Novel Orang-orang Oetimu Karya Felix K. Nesi - Boimau, Nirwandi; Nitbani, Semuel H.; Pekuwali, Dian Sari A. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
The focus of this research is “How are the forms of compliance and violation of the principle of cooperation between characters ini the dialogue of the novel Orang-orang Oetimu by Felix K. Nesi”. The aim of this research is to describe the forms of compliance and violation of the principle of cooperation between characters ini the dialogue of the novel Orang-orang Oetimu by Felix K. Nesi. The teory used is Grice’s theory of the principle of cooperation, because what is analyzed is the speech (dialogue) between characters in the novel. The method used in this study is a qualitative descriptive method. The results of the study show that there are 37 dialogue excerpts analyzed, consisting of 22 dialogue excerpts that comply with the principle of cooperation with details of 8 maxims of quantity, 5 maxims of quality, 8 maxims of relevance, 1 maxim of manner, and as many as 15 dialogue excerpts that violate the principle of cooperation with details of 5 violations of the maxim of quantity, 2 violations of the maxim of quality, 2 violations of the maxim of relevance and 6 violations of the maxim of manner.